Cinema noir : as marcas da morte e do hedonismo na atualização do gênero - Augusti, Alexandre Rossato (2013)
It is a rich supply of possibilities for study on noir film, even considering the lack of research in the country about it. Thus, this study aims to understand the context of noir film, considering to update the genre and based on its constitution, on the one hand supported by death, violence and crime, and secondly, hedonism and the femme fatale. It is intended as a further check up to contextualizes the film called neonoir point, as of theoretical orientations (using authors like James Ellroy; Heredero Carlos and Antonio Santamarina; Alain Silver and James Ursini; Luiz Nazario; and Marcia Ortegosa) and analysis of proposals, the possibilities of considering the continuity of noir film, as a classic noir film. From the methodological support of film analysis, based mainly on Aumont and Marie (2004), and Vanoye and Goliot-Lété (1994) proposed that the analysis of the movies The maltese falcon (John Huston, 1941), Gilda (Charles Vidor, 1946), Chinatown (Roman Polanski, 1974) and Lost highway (David Lynch, 1997). Among the key findings, indicates that noir can be considered both contemporaneously through what is usually called neonoir - when taking into account a wealth of information on rearranged noir movies upgraded according to technology, culture, politics, and that still may belong to other genres - such as through a spread less classifiable, in which some elements are realized in several movies, which are not identified as neonoir.